2021
DOI: 10.1039/d0ta10316k
|View full text |Cite
|
Sign up to set email alerts
|

How oxidation state and lattice distortion influence the oxygen evolution activity in acid of iridium double perovskites

Abstract: In view of iridium's scarceness and high cost, Ir-containing catalysts for water electrolyzers should have low loadings and maximal utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 73 publications
0
46
0
Order By: Relevance
“…Analyzing these results (results can be found in Supporting Information, Table S8), we have observed tensile strain in the second region atoms and compressive strain in the third region atoms for most of the active catalysts compared to the pure Cu system. Rojas and co-workers 69 have shown that distortion on the catalytic surface can improve the activity of the catalyst. Therefore, the distortion in the microstructure could be the reason for the enhancement of catalytic activity of these catalysts.…”
Section: Feature Importance and The Correlation Matrixmentioning
confidence: 99%
“…Analyzing these results (results can be found in Supporting Information, Table S8), we have observed tensile strain in the second region atoms and compressive strain in the third region atoms for most of the active catalysts compared to the pure Cu system. Rojas and co-workers 69 have shown that distortion on the catalytic surface can improve the activity of the catalyst. Therefore, the distortion in the microstructure could be the reason for the enhancement of catalytic activity of these catalysts.…”
Section: Feature Importance and The Correlation Matrixmentioning
confidence: 99%
“…Hence, the formation of *HCO from *CO is preferred on Cu-dNC as the distorted surface can stabilize the intermediates as also reported by Rojas and coworkers, who have shown that the lattice distortion of the catalyst can influence the activity, and higher distortion results in higher catalytic activity. 68 Moreover, the average coordination number (CN) of Cu-dNC (CN = 7) is less than that of the periodic Cu(100) surface (CN = 8). This is due to the higher extent of deformation within Cu-dNC.…”
Section: Comparison Among C 1 -And C 2 -Based Productsmentioning
confidence: 99%
“…The improvement in activity with testing is hypothesized to be caused by Sr leaching into the acidic electrolyte, leaving behind a highly active surface iridium oxide polymorph. , Many questions remain in the explanation of its heightened OER activity and stability in acid, including the identification of specific active sites, surface structural changes, and the role of electronic structure and oxidation state of surface Ir sites. While orthorhombic SrIrO 3 requires massive energy inputs or lattice stabilization methods to achieve syntheses, B-site alkaline earth and transition metal substitution enables syntheses at reasonable temperatures and pressures to obtain powder forms of SrIr x M 1– x O 3 , where M is the partially substituted metal. …”
Section: Introductionmentioning
confidence: 99%